Literature Review: Comparative Analysis of Sputum Cytology Examination Methods & Fine Needle Aspiration (Fnab) For Lung Cancer - Khairunnisa; Guli, Musjaya M. (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Cancer remains one of the biggest medical challenges, with high mortality rates due to late detection and limited treatment. In 2020, Indonesia saw 396,914 new cancer cases and 234,511 cancer deaths. The purpose of this paper is to provide a strong foundation for the research being conducted, by utilizing knowledge and findings from previous studies related to the FNAB method and sputum cytology in patients with lung cancer. The sources used in this writing are Google, NIH, NCBI, and other national journals. The selection of methods must be adjusted to the patient's condition, risk factors, and the availability of medical facilities, with the main objective of achieving a rapid, accurate, and precise diagnosis, so as to determine the most appropriate therapy for lung cancer patients. This study shows that FNAB and sputum cytology have their respective advantages in the diagnosis of lung cancer. FNAB is highly effective for diagnosing small lung nodules, especially in high-risk patients, due to its high accuracy and ability to provide more detailed diagnostic information. In contrast, sputum cytology is more suitable for early detection and screening in high-risk populations, although its accuracy is lower and limited to certain types of cancer